The four-component instructional design model (4C/ID): A meta-analysis on use and effect - Costa, J. M.; Miranda, G.; Melo, M. (Learning Environments Research, 2022)
The four-component instructional design model (4C/ID) has been increasingly used in face-to-face and online learning environments. We present a meta-analysis on the use and effect of educational programs developed with the 4C/ID model on performance, after more than 20 years of its application and research in different academic areas and technical training. We performed the meta-analysis through the combination of the effect sizes of the studies using Cohen’s d. The combination of the studies suggests that the use of educational programs developed with 4C/ID has a high impact on performance (d = 0.79), regardless of the academic area, the design of the study and the outcome (knowledge and complex skills). The grade under study was a significant moderator on the effect, showing that the higher-education level is more suitable for application of the 4C/ID model. Our results suggest that the use of the 4C/ID model should be prioritized as instructional model in college and university learning environments.